2014
DOI: 10.4149/av_2014_01_14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a DNA microarray-based multiplex assay of avian influenza virus subtypes H5, H7, H9, N1, and N2

Abstract: Summary. -Outbreaks of highly pathogenic avian influenza have caused considerable economic losses in the poultry industry and have also resulted in human deaths since 2004. Rapid subtyping of highly pathogenic avian influenza viruses(HPAIVs) in clinical specimens is a prerequisite of prompt control of disease and prevention of its spreading. In this study, we describe development of a DNA microarray-based detection and subtyping of HPAIVs in field samples. DNA copies of matrix (M) protein genes for the H5, H7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These assays typically rely on a single amplified target as an indicator of the presence of a pathogen. While numerous microarray-based assays utilizing multiple probes per target for the detection of human and animal-origin influenza have appeared (Mukherjee and Chakrabarti, 2012;Heydarov et al, 2017;Paulin et al, 2014;Shi et al, 2014;Ryabinin et al, 2011;Gall et al, 2009;Li et al, 2009), none are broadly commercially available. Next generation sequencing of influenza viruses provides the ability for complete characterization and is now routine in the three National Influenza Surveillance Reference Centers and at the CDC.…”
Section: Introductionmentioning
confidence: 99%
“…These assays typically rely on a single amplified target as an indicator of the presence of a pathogen. While numerous microarray-based assays utilizing multiple probes per target for the detection of human and animal-origin influenza have appeared (Mukherjee and Chakrabarti, 2012;Heydarov et al, 2017;Paulin et al, 2014;Shi et al, 2014;Ryabinin et al, 2011;Gall et al, 2009;Li et al, 2009), none are broadly commercially available. Next generation sequencing of influenza viruses provides the ability for complete characterization and is now routine in the three National Influenza Surveillance Reference Centers and at the CDC.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that this method had great potential for the rapid typing of high-pathogenicity AIV. In the study conducted by Shi et al [93], a gene chip is established; the method uses the RT-PCR amplification of the H5 H7, and H9 genes and the N1, N2, and M genes, marking it on the aldehyde slides on DNA chips. This method can simultaneously detect many kinds of AIV, including the H5N1 subtype.…”
Section: Gene Chipmentioning
confidence: 99%
“…With the rapid development of microarray technology, an increasing number of veterinary medicine studies have investigated host gene transcriptional responses to infection by various avian viruses[ 11 14 ]. REV, avian leucosis virus (ALV), and Marek’s disease virus (MDV) are the main causes of neoplastic diseases in avian hosts.…”
Section: Introductionmentioning
confidence: 99%